Factor that influence purchase intention of counterfeit product among university students in Kedah / Nur Nasuha Idris - Idris, Nur Nasuha (2015)
The study aims to investigate the factor that influence purchase intention of university students in Kedah towards counterfeit products. A conceptual model is proposed by Phau et al, 2009. A survey of 150 respondents was conducted in the Universiti Utara Malaysia (UUM). Pearson correlation, multiple regression test were used to test the hypotheses postulated and research question. It is discovered that price, subjective norm, personal gratification, product preference and perceived risk are the independent variables that strongly influence consumers' attitude towards counterfeit product. By having a better understanding of the consumers' behavioral intentions of buying counterfeit products, the manufacturers and marketers of the genuine brand products can make better marketing strategies to entice the consumer to buy the original product and not the counterfeit version. Theoretical contribution of this study is an extension of knowledge of consumers' attitude with regards to counterfeit products.